Memahami Assunnah Melalui Pendekatan Asbab Al-Wurud - Sukti, Surya; Firdaus , Muhammad Fadhil; Helmi, Helmi (UNIVERSITAS SERAMBI MEKKAH, 2025)
Research on hadith or assunnah is very necessary, because hadith or assunnah is very necessary, because hadith reached the Muslim community through long paths and routes of transmission. It is natural that there are errors in the understanding of the hadith of the Prophet SAW. Hadiths did not increase in number after the death of Rasulullah SAW. Meanwhile, the problems faced by Muslims continued to grow in connection with road developments. Therefore, in understanding hadiths, an appropriate method of understanding is needed through a comprehensive approach, both textual and contextual, with various forms and rules. With the approach method through asbabul wurud or the causes of the emergence of a hadith, this will make it easier for us to understand the content or meaning of the hadith.